The Impact of Green Human Resources Management Practices In Strengthening Environmental Organisational Citizenship Behaviours Through Organisational Culture as a Mediating Variable:The Palestinian Ministry of Health in the Gaza Strip as a Field Study - Fares, Mohammed (The Arab Journal of Administration, 2023)
The study aimed to determine the impact of green human resource management practices in strengthening the environmental organisational citizenship behaviours through organisational culture as a mediating variable applied to the Palestinian Ministry of Health in the Gaza Strip. To achieve the study objectives, the analytical descriptive approach was adopted, and a questionnaire was distributed as a study tool to the whole study population of (132) male and female employees as a comprehensive approach. The reality of the practice of green human resources management in the ministry was medium with a relative weight of (62.6%), and that the reality of applying environmental organisational citizenship behaviours was high with a relative weight of (71.6%) and that the reality of organisational culture was medium with a relative weight of (62.8%), and the results showed a positive impact of green human resource management practices in strengthening environmental organisational citizenship behaviours through the existence of organisational culture as a mediating variable. The study recommended that the ministry should adopt a green organisational culture that works to consolidate the values, principles and behaviours that consolidate the concepts of the green environment, and work to integrate green environmental practices into the ministry’s strategy.